Non-destructive in situ monitoring of structural changes of 3D tumor spheroids during the formation, migration, and fusion process - Ning, Ke; Xie, Yuanyuan; Sun, Wen; Feng, Lingke; Fang, Can; Pan, Rong; Li, Yan; Yu, Ling (eLife, 2025)
For traditional laboratory microscopy observation, the multi-dimensional, real-time, in situ observation of three-dimensional (3D) tumor spheroids has always been the pain point in cell spheroid observation. In this study, we designed a side-view observation petri dish/device that reflects light, enabling in situ observation of the 3D morphology of cell spheroids using conventional inverted laboratory microscopes. We used a 3D-printed handle and frame to support a first-surface mirror, positioning the device within a cell culture petri dish to image cell spheroid samples. The imaging conditions, such as the distance between the mirror and the 3D spheroids, the light source, and the impact of the culture medium, were systematically studied to validate the in situ side-view observation. The results proved that placing the surface mirror adjacent to the spheroids enables non-destructive in situ real-time tracking of tumor spheroid formation, migration, and fusion dynamics. The correlation between spheroid thickness and dark core appearance under light microscopy and the therapeutic effects of chemotherapy doxorubicin and natural killer cells on spheroids’ 3D structure was investigated.
Keywords: 3D spheroids; side-view; DU 145; NK-92